2016
DOI: 10.1074/jbc.m115.707091
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Insights into the Regulation of the Fundamental Rho Regulator RhoGDIα by Lysine Acetylation

Abstract: Rho proteins are small GTP/GDP-binding proteins primarily involved in cytoskeleton regulation. Their GTP/GDP cycle is often tightly connected to a membrane/cytosol cycle regulated by the Rho guanine nucleotide dissociation inhibitor ␣ (RhoGDI␣). RhoGDI␣ has been regarded as a housekeeping regulator essential to control homeostasis of Rho proteins. Recent proteomic screens showed that RhoGDI␣ is extensively lysine-acetylated. Here, we present the first comprehensive structural and mechanistic study to show how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…Acetylation of critical lysine residues in Ran modulates its activities related to the regulation of nuclear transport processes [19 ]. Similarly, acetylation of the guanine nucleotide dissociation inhibitor a impairs its binding to RhoA, thereby indirectly enhancing Rho-mediated alteration of actin filaments [20].…”
Section: Genetically Encoded Natural Protein Modifications and Their mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylation of critical lysine residues in Ran modulates its activities related to the regulation of nuclear transport processes [19 ]. Similarly, acetylation of the guanine nucleotide dissociation inhibitor a impairs its binding to RhoA, thereby indirectly enhancing Rho-mediated alteration of actin filaments [20].…”
Section: Genetically Encoded Natural Protein Modifications and Their mentioning
confidence: 99%
“…For example, fluorinated UAAs (20) have been used to study the interaction of phosphorylated GPCR tail-peptides with b-arrestin-1 and how this modulates the conformation and downstream signalling of the latter (Figure 4b) [67 ]. The tert-butyl group of (21) can be used in 1 H-NMR spectroscopy of proteins without any isotope labelling.…”
Section: Spectroscopic Analyses Of Protein Structure and Dynamicsmentioning
confidence: 99%
“…Therefore, another promising strategy is to design mechanistic inhibitors by combining substrate-based peptides with acetyl-lysine analogues such as trifluoroacetyl-lysine and thioacetyl-lysine, which show a markedly reduced rate of deacetylation (32, 66 -68). We and others show that some sirtuins present a remarkable level of substrate specificity for certain acetylation sites (14,15,69). However, whether structural features or the primary sequence is the main determinant of specificity remains an unresolved question.…”
mentioning
confidence: 99%
“…These findings are distinct from recently published effects on Rho guanine nucleotide dissociation inhibitor a (RhoGDIa), where it was observed that its acetylation can be stimulated by overexpression of PCAF, p300 and CBP and inhibited by overexpression of HDAC6 or SIRT2. 22 It is noteworthy that we did not observe significant relocalization of the Net1 isoform following acetylation. This may be due to differences in the number of NLS sequences between isoforms, as Net1 contains 4 NLS sequences while Net1A only has 2.…”
Section: Regulatory Mechanisms Controlling the Nuclear Localization Omentioning
confidence: 59%
“…24,25 In addition, the ability of RhoGDIa to bind RhoA is inhibited by lysine acetylation, leading to activation of RhoA and F-actin accumulation. 22 It is perhaps not surprising that the activity of Rho regulatory proteins is controlled by acetylation, as acetylation is an important regulatory mechanism for other cytoskeletal elements (Fig. 2).…”
Section: Regulatory Mechanisms Controlling the Nuclear Localization Omentioning
confidence: 99%